PEMBERDAYAAN INDUSTRI KECIL MENENGAH MELALUI AKSI NYATA DESA BERDAYA (PELATIHAN DIGITAL MARKETING DAN PERIJINAN BERUSAHA PADA PELAKU INDUSTRI MAKANAN DI DESA PELEYAN) - Fandiyanto, Randika; Irawan, Bambang; Masnilah, Rachmi; Yulisetiarini, Diah; Sudarsih, Sudarsih; Prasetyaningtiyas, Susanti (MIMBAR INTEGRITAS : Jurnal Pengabdian, 2025)
This activity was carried out for food industry players in Peleyan Village, Kapongan District, Situbondo Regency. The implementation of the training activity was in collaboration with the Peleyan Village Government, Rumah BUMN, Situbondo, Abdurachman Saleh University, Situbondo and Jember University. The training activity was held on Saturday, May 17, 2025 at the Peleyan village hall. Attended by 30 participants, housewives who are food and beverage business actors in the village area. The purpose of this activity is to provide education about the importance of food business permits such as Business Identification Number (NIB), Household Industry Products (PIRT) and Halal Certification as well as how to make promotional videos. The participants were also given an understanding of the material and practicum in promoting their products through social media Instagram, Tiktok through e-commerce media such as Shopee and Tokopedia. The participants were very enthusiastic in participating in the training activities, marked by several video results of their products that began to be uploaded on each participant's social media. The results of this activity are expected to be able to improve the progress of the small and medium industry sector, especially in the food business in Peleyan Village, Kapongan District, so that they can utilize their legality and digital marketing capabilities in improving their business performance.